2012
DOI: 10.1111/j.1600-051x.2012.01878.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐induced gingival overgrowth: a study in the French Pharmacovigilance Database

Abstract: Gingival overgrowth is often a "non serious" ADR but evolution was favourable in only half of cases. This ADR is "labelled" for calcium channel blockers, cyclosporine and phenytoin but can also occur with other immunosuppressants or anticonvulsants, antibiotics, oral contraceptives, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
0
15
0
5
Order By: Relevance
“…, Bondon‐Guitton et al. ). Few, if any papers have dealt with the long‐term management of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Bondon‐Guitton et al. ). Few, if any papers have dealt with the long‐term management of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this study is that the same specialist diagnosed, treated and observed these patients over a long period of time. Some of the previous studies have used medical registers to assess side effects (Kaur et al 2010, Bondon-Guitton et al 2012. Few, if any papers have dealt with the long-term management of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are an assortment of medications that have been reported to affect the size of the gingival tissues. 68 In the literature, the drugs primarily associated with gingival tissue enlargement have included the antiepileptic drugs phenytoin and sodium valproate, certain calcium channel-blocking drugs (e.g., nifedipine, verapamil, diltiazem, amlodipine, felodipine), immunoregulating drugs (e.g., ciclosporine), and high-dose oral contraceptives. [69][70][71] For drug-influenced gingival conditions, plaque bacteria in conjunction with the drug are necessary to produce a gingival response.…”
Section: Drug -Influen Ced G Ing Ival Enl Arg Ementsmentioning
confidence: 99%
“…Drug-influenced gingival enlargement is an adverse event noted from 7% to 70% in patients taking calcium channel blockers, cyclosporine, and phenytoin. 1 Mycophenolate mofetil, prednisone, and other drugs comprise the list of suspected drugs to cause gingival enlargement. 1 Cyclosporine is one of the most commonly used immunosuppressant drugs in organ transplant patients for prevention of transplant rejection.…”
Section: Introductionmentioning
confidence: 99%